1994
DOI: 10.1213/00000539-199405000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypothermic Metabolic Suppression on Hippocampal Glutamate Concentrations After Transient Global Cerebral Ischemia

Abstract: The cerebroprotective effects of mild and moderate hypothermia cannot be explained solely by a temperature-induced decrease in cerebral metabolic rate. This study examined the effects of graded hypothermia (32 degrees C, 28 degrees C, and 22 degrees C, vs 38 degrees C) on periischemic extracellular hippocampal glutamate concentrations in the New Zealand White rabbit. Global cerebral ischemia (15 min) was produced by a combination of neck tourniquet inflation and induction of systemic hypotension. Glutamate, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…37,41,[43][44][45] Hypothermia is thought to play a neuroprotective role after ROSC by decreasing metabolic demand, 46,47 decreasing the release of excitatory neurotransmitters, 16 and decreasing inflammation. 48 Animal studies since the 1980s [49][50][51][52][53][54][55][56][57] have suggested that mild induced hypothermia may be beneficial as a neuroprotectant after cardiac arrest. In addition, human literature describes a beneficial effect of mild induced hypothermia in resuscitated post cardiac arrest patients.…”
Section: Discussionmentioning
confidence: 99%
“…37,41,[43][44][45] Hypothermia is thought to play a neuroprotective role after ROSC by decreasing metabolic demand, 46,47 decreasing the release of excitatory neurotransmitters, 16 and decreasing inflammation. 48 Animal studies since the 1980s [49][50][51][52][53][54][55][56][57] have suggested that mild induced hypothermia may be beneficial as a neuroprotectant after cardiac arrest. In addition, human literature describes a beneficial effect of mild induced hypothermia in resuscitated post cardiac arrest patients.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroprotection would appear to function by enhancing maintenance of intracellular ATP levels during short HI episodes [19,[27][28] . Mild hypothermia also suppresses the release of free oxygen radicals, cytokines and excitatory neurotransmitters [29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that brain hypothermia improves neurologic outcome after successful resuscitation from cardiac arrest. 5,6 The mechanism by which this occurs is likely multifactorial and includes: reduced cerebral oxygen uptake (7% /ЊC), 25 attenuated cerebral energy failure, 26 reduced cerebral edema, 27 slowed adenosine triphosphate (ATP) depletion/depolarization, 28 delayed ischemic intercellular calcium elevation/intercellular acidosis, 29 reduced release of excitatory amino acids, including glutamate, glycine, and aspartate, 28,30,31 attenuated free radical-induced damage to lipids, 32,33 reduced activation of nitric oxide, 34 and decreased protein kinase C activity. 34 The optimal method by which hypothermic therapy is instituted continues to be debated.…”
Section: Discussionmentioning
confidence: 99%